Measurement of the Loss on Ignition of Bulk Calcined Bauxite Samples by Neutron Moderation - Borsaru M (The Australasian Institute of Mining and Metallurgy, 1985)
The production of high-grade calcined bauxite is very dependent on the moisture content of the final product. Existing procedures rely on the ignition of small samples to monitor the effectiveness of the calcination process. The results obtained by this gravimetric technique are several hours behind production and do not permit regular adjustment of the furnace to optimize the control of the chemically bound water content (LOI).To provide rapid and hence more relevant results, a neutron moderation technique has been developed for measuring the LOI of bulk samples of calcined bauxite while they are still hot. The method uses fast neutrons from an 241 Am-Be neutron source to irradiate the samples, and the backscattered thermal neutrons detected are a measure of bound moisture content.The rms deviation between neutron and conventional determinations of LOI, in 15 calcined bauxite samples, was 0.08 per cent LOI over the range 0.1 to 0.9 per cent LOI. When allowance is made for the rms error in the ignition method, the error in the neutron method is found to be 0.07 per cent LOI.